Epidermal Acyl-CoA-binding protein is indispensable for systemic energy homeostasis - Ditte Neess; Vibeke Kruse; Ann-Britt Marcher; Mie Rye Wæde; Julie Vistisen; Pauline M. Møller; Rikke Petersen; Jonathan R. Brewer; Tao Ma; Georgia Colleluori; Ilenia Severi; Saverio Cinti; et al. (Elsevier, 2021)
Objectives: The skin is the largest sensory organ of the human body and plays a fundamental role in regulating body temperature. However, adaptive alterations in skin functions and morphology have only vaguely been associated with physiological responses to cold stress or sensation of ambient temperatures. We previously found that loss of acyl-CoA-binding protein (ACBP) in keratinocytes upregulates lipolysis in white adipose tissue and alters hepatic lipid metabolism, suggesting a link between epidermal barrier functions and systemic energy metabolism. Methods: To assess the physiological responses to loss of ACBP in keratinocytes in detail, we used full-body ACBP−/− and skin-specific ACBP−/− knockout mice to clarify how loss of ACBP affects 1) energy expenditure by indirect calorimetry, 2) response to high-fat feeding and a high oral glucose load, and 3) expression of brown-selective gene programs by quantitative PCR in inguinal WAT (iWAT). To further elucidate the role of the epidermal barrier in systemic energy metabolism, we included mice with defects in skin structural proteins (ma/ma Flgft/ft) in these studies. Results: We show that the ACBP−/− mice and skin-specific ACBP−/− knockout mice exhibited increased energy expenditure, increased food intake, browning of the iWAT, and resistance to diet-induced obesity. The metabolic phenotype, including browning of the iWAT, was reversed by housing the mice at thermoneutrality (30 °C) or pharmacological β-adrenergic blocking. Interestingly, these findings were phenocopied in flaky tail mice (ma/ma Flgft/ft). Taken together, we demonstrate that a compromised epidermal barrier induces a β-adrenergic response that increases energy expenditure and browning of the white adipose tissue to maintain a normal body temperature. Conclusions: Our findings show that the epidermal barrier plays a key role in maintaining systemic metabolic homeostasis. Thus, regulation of epidermal barrier functions warrants further attention to understand the regulation of systemic metabolism in further detail.